2019
DOI: 10.1007/s10578-019-00925-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Problematic Drinking in Early Adolescence: A Systematic Approach

Abstract: Alcohol use during early adolescence is associated with other risk behaviors as well as future health problems. Within the design of a larger prospective research program, a cohort of U.S. inner-city sixth-grade students (N = 1573, mean age = 12.10) were assessed and reassessed in the seventh-grade. Self-reported information was obtained on problems related to alcohol, fixed markers of risk (e.g. sex, age, SES), individual and interpersonal factors (e.g. internalizing and externalizing symptoms) and contextual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“… 5 , 6 Several risk factors for underage drinking have been identified, such as childhood physical abuse, parenting factors, peer influences, conduct problems, and depression. 9 , 34 , 35 Fortunately, there is some evidence suggesting that the implementation of interventions including family-based prevention programs, mentoring, mHealth technology (e.g., mobile applications, social networking websites, text messages, etc. ), and public health measures (e.g., restrictions on alcohol availability, taxation to increase prices, etc.)…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Several risk factors for underage drinking have been identified, such as childhood physical abuse, parenting factors, peer influences, conduct problems, and depression. 9 , 34 , 35 Fortunately, there is some evidence suggesting that the implementation of interventions including family-based prevention programs, mentoring, mHealth technology (e.g., mobile applications, social networking websites, text messages, etc. ), and public health measures (e.g., restrictions on alcohol availability, taxation to increase prices, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Peers and family have been recognized as two critical social agents capable of influencing the initiation of alcohol consumption and the transition to alcohol problems in early adolescence [14][15][16]33 . Parents usually are a source of alcohol for young adolescents 32,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Binge drinking is known to be determined by a large variety of factors both within the individual (e.g., genetic disposition, mood traits, behavioral problems, and neuropsychological deficits) and the environment (e.g., family history of alcoholism, peer and other social relationships, society, and neighborhood) [14][15][16] . As some risk factors are hard or impossible to change, research to identify protective factors that can delay, reduce, or prevent binge drinking is a crucial health objective 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents have also been demonstrated to engage in alcohol and substance use at relatively high levels (Guerin & White, 2020 ; Swendsen et al, 2012 ). Substance use and mental health problems such as depression have a bi‐directional relationship with significant implications for adolescent wellbeing and transition to adulthood (Isaksson et al, 2020 ; Liu et al, 2018 ). Further, Sellers et al (Sellers et al, 2019 ) in their study of cross‐time changes in outcomes following mental health problems during childhood using three UK longitudinal cohort studies and covering four decades of child mental health prevalence data, demonstrated that the experience of mental health issues during childhood has become more strongly associated with social, educational and mental health problems over time.…”
Section: Background For the Reviewmentioning
confidence: 99%